The split time : economic philosophy for human flourishing in African perspective - Wariboko, Nimi, 1962- (State University of New York Press, 2022)
"Aims to construct an economic philosophy from indigenous African thought"-- Provided by publisher.
Keywords: Economics -- Philosophy.; Philosophy, African.; Économie politique -- Philosophie.; Philosophie africaine.; Economics -- Philosophy; Philosophy, African